Asphalt encounters: Chinese road building in Ethiopia - Driessen, M (2014)
Over the past decade, road construction has come to represent Chinese engagement with Ethiopia. This study considers the lives of Chinese workers at the lower end of one such project in Tigray, northern Ethiopia. By examining the ways in which Chinese road workers tried to make sense of daily life on the construction site, I reveal the inherent contradictions of a state rhetoric that promoted 'win-win cooperation' ('huying huli hezuo') and 'friendly collaboration' ('youhao hezuo') between China and Africa, and demonstrate the local manifestations of the much-debated 'China Model'. Initial expectations coloured by state narratives, as well as the migrants' own experiences with domestic development, stood in sharp contrast to realities on the ground. Convinced of the goodwill nature of their activities, Chinese workers were puzzled by and resentful of the apparent ingratitude of local Ethiopians, their lack of cooperation, and, worse, repeated attempts to sabotage the construction work. Chinese workers' struggles with development in Africa, I argue, should be understood in relation to their background as upwardly mobile rural migrants at the bottom of the corporate hierarchy, successors of engineers dispatched under Mao Zedong who had enjoyed a respectable reputation at home – a reputation current workers felt they were about to lose – and as citizens aware of their country’s status in the world as superior to Africa and inferior to the West. The workers sought to live up to Chinese ideals of development by demonstrating and promoting the virtues of self-development, simultaneous development, and entrepreneurialism. Ethiopians, however, did not concede to these ideas, and their lack of cooperation stirred resentment and expressions of self-pity on the part of the Chinese, who blamed the Ethiopian labourers, their suzhi (human quality), and wenhua (culture) for the limited success of the projects. What Chinese workers failed to realise was that the attitude of Ethiopians was in fact a response to asymmetrical and contested power relations that did not allow for win-win cooperation and friendly collaboration.